Innovation of Lathe Dual Tool Holder as a Catalyst for Efficiency in Teaching and Learning of Lathe Machine Operations - Hamid bin Salamon; bin Mokhtar, Mohamad Nazri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Carbide cutting tools are commonly used in machine workshops, especially within the Department of Mechanical Engineering at Politeknik Ibrahim Sultan. These tools function with the aid of a tool holder, but the existing holders can only accommodate one cutting insert at a time. This study aims to improve the design of the existing tool holder by creating a more practical and cost-efficient alternative, referred to as the Lathe Dual Tool Holder. This improved design enables the mounting of two types of carbide inserts—TPMR160308 (triangular) and SPMR120304 (square)—thus eliminating the need to change holders during operations. The innovation results in time savings, reduced storage requirements, increased screw durability, and overall cost efficiency. Ultimately, the Lathe Dual Tool Holder enhances the machining process by simplifying tool changes, increasing productivity, and supporting better teaching outcomes in technical and vocational education.